A formative evaluation of a family-based walking intervention-Furness Families Walk4Life - Milton, Karen (BioMed Central, 2011)
BACKGROUND: The family unit may be an important mechanism for increasing physical activity levels, yet little is known about what types of family-based interventions are effective. This study involved a formative evaluation of a 12 week intervention to encourage walking as a family based activity. The intervention consisted of several key elements including led walks and tailored resources, as well as remote support provided via the telephone. The project aimed to explore factors associated with successful delivery of the programme and to identify areas of improvement for future implementation. METHODS: A total of nine interviews were undertaken with programme staff who were involved in either the set up or delivery of the intervention. In addition, four interviews and two focus groups were undertaken with participants to explore their experiences of the programme. The analysis involved both deductive and inductive reasoning. RESULTS: In total, 114 people participated in the programme, which included 36 adults, 10 adolescents and 68 children (≤ 10 years of age). Adult participants reported several barriers to walking including concerns over their children's behaviour and their ability to maintain 'control' of their children. Walking in a group with other families gave parents confidence to go out walking with their children and provided a valuable opportunity for social interaction for parents and children alike. The most successful walks incorporated specific destinations and an activity to undertake upon reaching the destination. Incorporating other activities along the way also helped to keep the children engaged. CONCLUSIONS: The results of this study have highlighted the important contribution that formative research can make in informing and refining a programme to increase appropriateness and effectiveness. The study has helped to highlight the key characteristics associated with delivering a successful walking intervention to young families. It is recommended that practitioners undertake formative research when developing novel health promotion initiatives to help refine the programme protocols.